An Experimental Approach of Fibre Optics Refractometers - Behera, Bhagyalaxmi; Satrusalya, Sarmista (International Journal of Psychosocial Rehabilitation, 2025)
Refractometers are optical devices that measures the refractive index of the multiple transparent and semi-transparent resources either of solid or liquid state. Traditional refractometers operates on the principle of measuring “an optical critical angle”, “Brewster’s angle”, “angular deviation of the light beam” etc. According to the last few decades, there is a speedy growth in the sensing technology of the fibre optics techniques led for developing the fibre optics refractometer. Within comparison sensors performs multiple recompenses to the traditional refractometers. In this literature, a brief assessment of few fibre optic refractometers are reported. These reviews entails detailed and accurate knowledge to the readers of the working principles, constructional methods and distinctive features of multiple fibres optic refractometers as reported till date.